"Chorea": A Unique Presentation of Left Atrial Myxoma in a Pediatric Patient. Issue 4 (July 2020) - Chikkabyrappa, Sathish M.; Tretter, Justin T.; Vishwanath, Vijay; Bhatla, Puneet
We report an unusual presentation of a large left atrial myxoma in an eight-year-old girl who presented with the sudden onset of chorea. This case illustrates the fact that the presentation of chorea in nonendemic areas for rheumatic fever should raise suspicion for a myxoma. The chorea resolved soon after removal of the myxoma, supporting the hypothesis of an immune-mediated mechanism, or manifestation of paraneoplastic syndrome secondary to the myxoma.